Analysis of 5′-End Sequences of Chimpanzee cDNAs - Sakate, Ryuichi (Cold Spring Harbor Laboratory Press, 2003)
We constructed full-length enriched cDNA libraries from chimpanzee brain, skin, and liver tissues by the oligo-capping method to establish a database of sequences of chimpanzee genes. Randomly selected clones from the libraries were subjected to one-pass sequencing from their 5′-ends. As a result, we collected 6813 chimpanzee cDNA sequences longer than 400 bp. Homology search against human mRNA sequences (RefSeq mRNAs) revealed that our collection included sequences of 1652 putative chimpanzee genes. In order to calculate the sequence identity between human and chimpanzee homologs, we constructed 5′-end consensus sequences of 226 chimpanzee genes by aligning at least three sequences for individual genes. Sequence identity was estimated by comparing these consensus sequences and the corresponding sequences of their human homologs. The average sequence identity of the 5′-end cDNAs was 99.30%. Those of the 5′-UTRs and CDSs were 98.79% and 99.42%, respectively. The results confirmed that human and chimpanzee genes are highly conserved at the nucleotide level. As for amino acids, the average sequence identity was 99.44%. The average synonymous (K(S)) and nonsynonymous (K(A)) divergences were estimated to be 1.33% and 0.28%, respectively. [Supplemental material is available online at www.genome.org. All of the 1947 sequences used for constructing the consensus sequences of 226 chimpanzee genes have been submitted to DDBJ under accession nos. –. Two hundred twenty-six consensus sequences and their detailed annotation descriptions are available at our Web site http://www.prigen.org/.]